TRUST AND CONTROL ASPECTS IN JOINT VENTURE OF GARUDA INDONESIA AND SRIWIJAYA AIR - Dariyah, Dariyah; Indra Setiawan,; Suharto Abdul Majid, (International Journal of Social Science, 2024)
This research examines the aspects of trust and control in the joint venture cooperation pattern of Garuda Indonesia and Sriwijaya Air in managing organizational uncertainty. This research distinguishes trust from control. However, the two remain closely related as information from the control system can also be used to assess the level of trust. Qualitative research methods were used in this study by interviewing 6 (six) management ranks from Garuda Indonesia and Sriwijaya Air respectively, as well as focus group discussions with practitioners, academics, ministry of transportation, government, and stakeholders, and users. Specifically, this research addresses the role played by information from three types of controls (output, behavioral, and social) in determining two types of trust (competence and goodwill). Competence trust and goodwill trust are tested at the operational and executive levels, respectively, and in terms of information that builds and destroys trust. Findings from a case study of a joint venture between two airlines show that controls generate information that strengthens competence trust at the operational level, but leaves goodwill trust at the executive level relatively vulnerable to betrayal of goodwill trust.